2022
DOI: 10.1101/2022.08.09.503375
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exercise Training Remodels Inguinal White Adipose Tissue Through Adaptations in Innervation, Vascularization and the Extracellular Matrix

Abstract: Inguinal subcutaneous white adipose tissue (iWAT) is essential for conferring the beneficial effects of exercise training on metabolic health. Training alters adipocyte function, yet how the structural components of iWAT respond to training is not known. Using multi-omics approaches, we show that training in male mice results in iWAT remodeling, decreasing extracellular matrix (ECM) deposition, and increasing vascularization and innervation. We find adipose stem cells (ASC) to be the main ECM contributors and … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…We utilized the 10x Genomics Visium Spatial Gene Expression platform (10x Genomics, Pleasanton, CA, USA) for our spatial transcriptomics analysis. As previously described, the experiment involved the utilization of paraffin-embedded inguinal white adipose tissue (iWAT) obtained from sedentary and trained mice 4 . The Visium Spatial Gene Expression procedure was conducted following the manufacturer’s instructions (10x Genomics, Pleasanton, CA, USA) with the following parameters: adipose tissue sections of 20 μm thickness were used, and hematoxylin and eosin (H&E) staining was performed by immersing the slides in isopropanol for 1 minute, followed by a 3-minute incubation in hematoxylin and a 30-second incubation in eosin (diluted at 1:20).…”
Section: Experimental Model and Methods Detailsmentioning
confidence: 99%
See 3 more Smart Citations
“…We utilized the 10x Genomics Visium Spatial Gene Expression platform (10x Genomics, Pleasanton, CA, USA) for our spatial transcriptomics analysis. As previously described, the experiment involved the utilization of paraffin-embedded inguinal white adipose tissue (iWAT) obtained from sedentary and trained mice 4 . The Visium Spatial Gene Expression procedure was conducted following the manufacturer’s instructions (10x Genomics, Pleasanton, CA, USA) with the following parameters: adipose tissue sections of 20 μm thickness were used, and hematoxylin and eosin (H&E) staining was performed by immersing the slides in isopropanol for 1 minute, followed by a 3-minute incubation in hematoxylin and a 30-second incubation in eosin (diluted at 1:20).…”
Section: Experimental Model and Methods Detailsmentioning
confidence: 99%
“…Additionally, the proteins were filtered to maintain an FDR of less than 1%. Protein quantification was performed exclusively on peptides with a summed signal-to-noise (SN) threshold greater than 200 and an MS2 isolation specificity of 0.5.The mass spectrometry proteomics data were previously deposited to the ProteomeXchange Consortium via the PRIDE partner repository with the dataset identifier PXD040894 4 .…”
Section: Orbitrap-based Lc-ms/ms Subcutaneous Adipose Tissue Proteomi...mentioning
confidence: 99%
See 2 more Smart Citations
“…The findings by these authors emphasize the importance of physical activity in alleviating obesity (4). It has been shown that exercise acts as an effective stimulus of Inguinal white adipose tissue (iWAT) remodeling primarily through changes in extracellular matrix (ECM), vascularization, and innervation (5).…”
Section: Introductionmentioning
confidence: 99%